2008
DOI: 10.1093/geront/48.6.802
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Cognitive and Instrumental Functional Performance as Indicators for Driving Cessation Risk Across 3 Years

Abstract: Purpose The purpose of this study was to prospectively examine the role of cognitive and instrumental functional performance in driving cessation while simultaneously accounting for any contributions of demographics, vision, physical performance, and health among a sample of older adults without dementia. Design and Methods Included in the analyses were 1,838 participants from the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) study who were drivers at baseline and completed the third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 44 publications
2
52
1
Order By: Relevance
“…Prior research has indicated that poor cognitive functioning is associated with risk of driving cessation (Anstey et al , 2006; Ackerman et al , 2008; Edwards et al , 2008). However, our findings suggest that it may also be the case that driving cessation itself is a risk factor for accelerated cognitive decline over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has indicated that poor cognitive functioning is associated with risk of driving cessation (Anstey et al , 2006; Ackerman et al , 2008; Edwards et al , 2008). However, our findings suggest that it may also be the case that driving cessation itself is a risk factor for accelerated cognitive decline over time.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research on driving behavior and cognitive functioning has focused on cognitive impairment as a risk factor for driving cessation (Anstey et al , 2005; Anstey et al , 2006; Ackerman et al , 2008; Edwards et al , 2008). Driving itself is a cognitively challenging task which requires engagement of memory, speed of processing, and executive functioning (Anstey et al , 2005; Dickerson et al , 2007); thus, drivers with cognitive impairment are more likely to be involved in crashes (Duchek et al , 2003; Dickerson et al , 2007; Ott et al , 2008; Carr and Ott, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, former drivers have worse health status than never drivers, which is consistent with the previous reports (Forrest et al, 1997; Mann et al, 2005; Siren, Hakamies-Blomqvist, & Lindeman, 2004). The process of driving cessation is generally prompted by the accumulation of impairments in physical, cognitive, and sensory function (Ackerman, Edwards, Ross, Ball, & Lunsman, 2008; Ball & Rebok, 1994; Edwards et al, 2008), and thus it was not unexpected that overall former drivers reported worse health than never drivers. That is, being a former driver in and of itself is an indication of poor functional status, but that may not be true of never drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Although cognitive processing has been a main interest of driving researchers, training programs to enhance cognitive processing have mostly been studied in specialized driving populations such as older adults (Ackerman et al 2008;Edwards et al 2009;Vance et al 2010). The cognitive training programs, which may alter the manner in which internal and external distractions are handled, have proven to be useful in improving driving performance.…”
Section: Introductionmentioning
confidence: 99%